This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This question is one of the famous and recurring question. Wrote the P, Q, R, S into 9 ( 1 0 0 0 s + 1 0 0 r + 1 0 q + p ) = 1 0 0 0 p + 1 0 0 q + 1 0 r + s Provided that 0 ≤ p , q , r , s ≤ 9 , the expansion provides us instantly that s = 1 and p = 9 . Upon putting this two value in, it gives 9 ( 1 0 0 9 + 1 0 0 r + 1 0 q ) = 9 0 0 1 + 1 0 0 q + 1 0 r or simply 8 + 8 9 r = q With the conditions provided, we can conclude that r = 0 and q = 8 , hence p q r s = 9 8 0 1